Epithelioid Trophoblastic Tumour Presenting with Scalp Lesions - Raquel Basto (SMC MEDIA SRL, 2021)
Epithelioid trophoblastic tumour (ETT) is a very rare variant of gestational trophoblastic disease, which arises in reproductive-age women with a prior gestational history. Because of its rarity, its biological behaviour, imaging characteristics and therapeutic schedule have not yet been fully established. Here we describe a rare case of metastatic ETT in a premenopausal woman. A 40-year-old, gravida 3, para 2, Portuguese woman was referred to the dermatology department for multiple skin nodules on the scalp measuring between 1 and 6 cm. A skin biopsy was suggestive of metastatic lesions of low differentiated carcinoma in favour of squamous cell carcinoma. Staging cervical-thoracic-abdominal and pelvic CT showed multiple lesions compatible with metastasis (ganglia, lung and kidneys). Since a CT scan was unable to identify the primary tumour, it was decided to perform a PET-CT scan and to take a biopsy of a vulvar nodule which had been clinically identified as ETT. The patient began the EMA-CO protocol and completed two cycles but with clinical worsening and radiological progression. Although several different chemotherapy regimens are used to treat gestational trophoblastic disease, the optimal treatment is not known given the rarity of this disease and the lack of controlled trials.